Public Investment, Technological Innovations, and Environmental Degradation: Asymmetric ARDL Approach - Ullah, Saif; ur Rahman, Saif; Rehman, Chaudhary Abdul (Pakistan Journal of Humanities and Social Sciences, 2023)
Environmental degradation is the biggest problem for the entire world and especially for developing countries which are already facing many problems and challenges and the environmental problem is one of them. That’s why the present research scrutinizes the different factors which are affecting the environmental condition. However, the examination of the unequal effects of public investment, technology, and other controlled variables on environmental destruction in Pakistan is the main goal of the current study. The study uses the asymmetric (NARDL) technique with data from 1971 to 2021. Also, the study's findings indicate that the economy sampled produced varied outcomes. The study's findings, however, support the existence of an asymmetric (NARDL) relationship in Pakistan between public investment, ICT, economic expansion, sustainable sources, and environmental damage. Moreover, the existing study scrutinized nonlinearities that are missing in previous studies and showed some misleading inferences. Furthermore, this research examined at how technology, state investment, and other controlled variables affected Pakistan's environment in asymmetric ways. The study's findings also suggested that lawmakers adopt some laws that would urge the federal government to spend its money on carbon-free or low-carbon initiatives in order to maintain a sustainable environment.